PreyTouch: a touchscreen-based closed-loop system for studying predator-prey interactions - Regev Eyal; Nitzan Albeck; Mark Shein-Idelson (Communications Biology)
Abstract The ability to catch prey is crucial for survival and reproduction and is subject to strong natural selection across predators. Prey capture demands the orchestrated activation of multiple brain regions and the interplay between sensory processing, decision-making, and motor execution. These factors, together with the ubiquity of prey capture across species makes it appealing for comparative studies across neuroscience and ecology. However, despite recent technological advances, experimental approaches for studying natural behaviors such as prey catch are lagging behind. To bridge this gap, we created PreyTouch—a novel approach for performing prey capture experiments that incorporate flexible prey control, accurate monitoring of predator touchscreen strikes and automated rewarding. Further, its real-time processing enables coupling predator movement and prey dynamics for studying predator-prey interactions. Finally, PreyTouch is optimized for automated long-term experiments featuring a web UI for remote control and monitoring. We successfully validated PreyTouch by conducting long-term prey capture experiments on the lizard Pogona vitticeps. This revealed the existence of prey preferences, complex prey attack patterns, and fast learning of prey dynamics. PreyTouch’s unique features and the importance of studying prey capture behavior make it a valuable platform for connecting natural behavior with cognitive studies across various species and disciplines.